The Impact of E-language learning on Academic Writing of University Undergraduate students in Nigeria - Oyinloye, Comfort Adebola; Lasisi, Fatola Olugbenga (NIU Journal of Social Sciences, 2019)
Language learning is an essential part of human communication and any educational system. In this process, technological tools and symbol systems help provide proper linguistic symbols. This study investigated the impacts of e-Language learning on the academic writing of undergraduate University students in Nigeria. This study also investigated the utilization of information and communication technologies (ICT) for Language teaching and learning. Three hundred (300) students were randomly selected from the population of 3,002 undergraduate Linguistic students (300 level) in the Federal Universities, Nigeria. A set of questionnaires was divided into the two main sections: (i) Impact of E-Language Learning on Academic Writing (IELLAW) and (ii) Utilization of Information Communication Technology Resources in the Language Teaching and Learning (UICTRLTL) was used to collect the data. The instrument was face validated and content validated by three experts in Linguistics. Cronbach’s Alpha (α) was calculated to measure the overall internal consistency reliability of the questionnaire and 0.92 value of α suggested that the survey was a reliable instrument. The responses received from the students were categorized and the frequency counts, mean, standard deviation and pie chart were used to answer the research questions. The result of the study showed that e-language learning has positive impacts on the academic writing of Nigerian University students. The results of the study also revealed that the most utilized Information Communication and Technology (ICT) resources for teaching and learning language was Facebook. The study recommended amongst others that Language teachers should urge their learners to use technology in developing their language skills. Keywords: Impacts, E-Language, Learning, Academic Writing, University